PENERAPAN MEKANISME COMPLIANT PADA MEKANISME GERAK GRIPPER - Neil Harits Saptata (2022)
Innovation is a term for applying an idea that can form a new product or improve an existing product. The parallelogram shape is the most popular mechanism used in gripper because of its configuration that causes the tip to hold its orientation when closed and open. The drawback of this form is the large number of components needed and requires an assembly process in order to achieve the desired motion. A compliant mechanism can overcome this shortcoming because objects can be made simpler without the need for an assembly process. The advantages and disadvantages of the compliant gripper have been obtained from the design, test results, and comparisons. The design obtained with dimensions of P 186.27 X W 157.55 X H 10 mm uses a leaf-type flexure with varying thickness. The thicker it is the greater the force required to use the gripper. the results printed using a 3d printer also reflect the data that has been obtained regarding the style. The thinner the flexure, the more susceptible the tool is to external forces such as shocks. The comparisons made show that the advantages of the gripper are the minimum required components, no assembly process required, and a smaller mass compared to the reference mechanism. Disadvantages obtained are the decrease in the width of the opening distance and the orientation of the finger that changes according to changes in the angle at the fulcrum.